Neurorehabilitation for Central Nervous System Disorders - van der Brugge, Frans (Springer International Publishing, 2018)
This book describes the four most common central nervous disorders (Parkinson, stroke, dementia and multiple sclerosis) by focusing on the similarities of their symtoms. This analysis is necessary in order to determine the appropriate treatment method for individual patients. In physical therapy there are various methods available for treating patients affected by a neurological disease, yet the method presented here is the only one to include systematic interventions adapted to the patient's needs, which are determined by means of a health situation analysis. The book offers practical and applicable information for allied health professionals seeking interventions to help patients function better in their own environment. In addition, this book features updated information on the "van der Brugge method," focusing on a targeted program to stimulate movement in the elderly with dementia. This book will be of interest to neurologists and physiotherapists.